Screening of Heat-Tolerant Indica Rice Varieties in the Middle and Lower Yangtze River - Man Zhang; Kaixuan Feng; Xinde Dong; Yongjin Zhou; Jinhua Chen; Bin Teng; Zhong Li; Lantian Ren; Wenge Wu (Agronomy, 2022)
Rice growth is constantly challenged by severe environmental conditions, especially high-temperature stress, brought about by global warming. How to increase rice yields is a current issue in many countries. By analyzing the meteorological data from Anhui Province over the past 60 years, the frequency and level of high-temperature damage were comprehensively analyzed. On this basis, five indica rice varieties with strong high-temperature tolerance, relatively high yield and stable yield were selected by laboratory-simulated high-temperature and field high-temperature experiments: Longliangyou Huazan (LLYHZ), 9you-6 (9Y-6), Longliangyou-1988 (LLY-1988), Fengliangyou-4 (FLY-4) and Huanghuazan (HHZ). These are suitable for planting in the middle and lower reaches of the Yangtze River. This study provides a theoretical reference and scientific basis for the study of rice tolerance to high-temperature stress.